Central America during the nineties: the difficult task of evaluating a decade of paradoxes - Martí i Puig, Salvador (Estudios Latinoamericanos, 2002)
A decade ago of the firm of peace’s processes and institutional opening taken place in Central America is necessary to make a pause to reflect on three fundamental problems. In first place to analyze the nature of the resulting regimes, in the performance of their institutions as well as in the public policies that they have gone developing. In second place, to observe the conduct, the projects and the discourse of the principal political actors in the electoral sand. And, finally, to reflect on the existing social behavior, analyzing their longings, perceptions and demands respect the immediate future. Probably, of this exercise will appear a contradictory balance. Some tings have improved while others not. Precisely because of this it is necessary to think again the policy in Central America since the international context as well as the challenges of this is area have changed remarkably.